Jalan Pulang ke Fitrah: Pesan Sirrul Asrar bagi Generasi yang Lelah Mencari Diri - Faris Bahrul Ulum; Hasan, Muhammad Syahrul (Ma'had Aly Idrisiyyah, 2025)
Abstract This article examines the teachings of Sirrul Asrar by Shaykh Abdul Qadir al-Jilani as a spiritual map for modern humans experiencing existential crises, a loss of meaning, and disconnection from their primordial nature (fitrah). The study employs a qualitative-descriptive method based on library research, utilizing a thematic-sufistic and reflective-contextual approach to key sections of the text, such as the concepts of wathan al-asli (the original homeland), asfal as-safilin (the lowest state of being), the fourfold structure of knowledge (shari‘ah, tariqah, ma‘rifah, and haqiqah), and the hierarchy of the human soul (jasmani, ruwani, sultani, and qudusi). The findings reveal that Sirrul Asrar is not merely a normative Sufi text, but offers existential therapy that guides the soul toward self-purification, awareness of divine unity (tawhid), and holistic spiritual restoration. The concept of thiflul ma‘ani the birth of true spiritual consciousness represents the culmination of this inner journey toward human authenticity. These teachings are highly relevant in addressing contemporary issues such as spiritual alienation, digital self-construction, value disorientation, and existential fatigue caused by a fast-paced, consumerist culture. Thus, this classical Sufi legacy is crucial to be revived as an alternative narrative and spiritual solution for modern individuals who have lost direction and connection to their existential roots. Keywords: Sirrul Asrar, existential tawhid, thiflul ma‘ani, spiritual crisis, contemporary Sufism Abstrak Artikel ini mengkaji ajaran Sirrul Asrar karya Syekh Abdul Qadir al-Jailani sebagai peta spiritual bagi manusia modern yang mengalami krisis eksistensial, kehampaan makna, serta keterputusan dari akar fitrahnya. Penelitian ini menggunakan metode kualitatif-deskriptif berbasis studi pustaka, dengan pendekatan tematik-sufistik dan reflektif-kontekstual terhadap bagian-bagian penting dalam kitab seperti konsep wathan al-asli, asfal as-safilin, struktur empat cabang ilmu (syariah, thariqah, marifah, dan haqiqah), serta hirarki ruh manusia (jasmani, ruwani, sultani, dan qudusi). Hasil kajian menunjukkan bahwa Sirrul Asrar tidak hanya merupakan teks normatif sufistik tetapi juga mengandung tawaran terapi eksistensial yang membimbing manusia menuju penyucian diri, kesadaran tauhid, dan keutuhan spiritual. Konsep thiflul ma‘ani sebagai lahirnya kesadaran ruhani sejati menjadi titik kulminasi dari perjalanan menuju hakikat manusia. Ajaran ini relevan dalam menjawab problematika kontemporer seperti alienasi batin, pencitraan digital, disorientasi nilai, dan kelelahan spiritual akibat budaya instan dan konsumtif. Oleh karena itu, warisan sufistik klasik ini penting untuk dihadirkan sebagai narasi alternatif sekaligus solusi ruhani bagi manusia modern yang kehilangan arah dan akar eksistensinya. Kata Kunci: Sirrul Asrar, krisis identitas, tauhid eksistensial, peta ruh, sufisme kontemporer